ANALISIS PERSAINGAN INDUSTRI TELEKOMUNIKASI DI INDONESIA SWITCHING BARRIES DAN KEPUASAN KONSUMEN - Subuh Hidayat (LPPM UNIVERSITAS BINA INSAN, 2016)
This study aims to determine consumer behavior in using telecommunications service providers, especially those related to switching barries and consumer satisfaction.This study uses qualitative research methods specifically using ethnographic methods, namely to provide an opportunity to explore how things happen in each action, and thus the results of research that will be obtained in accordance with the reality that occurs. The sample used in this study is community or consumer participants in Lubuklinggau City, South Sumatra Province. Based on the results of the analysis, consciously or unconsciously the provider companies experienced